Investigating Learning Styles For Adaptive Massive Open Online Course (MOOC) Learning - Hashim, Hasmaini; Salam, Sazilah; Mohamad, Siti Nurul Mahfuzah (TAF Publishing, 2017)
Learners’ characteristics are important in all forms of online learning including MOOC learning. One of them is learning style that is a psychological factor, which causes learners to have a collection of preferences during a learning process. Previous studies reported that learning styles of learners from different disciplines have significant differences, and in some situations, their learning patterns can explain their academic achievement. Studies also recommended that teaching methods that match to learning styles increase students’ retention ability, increase their satisfaction, and helped in their success. In this study, our aim is to investigate the learning styles dimension of students in MOOC learning, and propose a MOOC development model that is adaptive to learning styles. A mixed-method approach was adopted in this study to investigate the learning styles dimension of students in MOOC learning based on Felder and Silverman (1988) Learning Style Model. Samples for the quantitative and qualitative studies were 50 and 20 students respectively. The interview consists of 14 questions and 11 students involved in the interview. The results from the survey analysis revealed that the highest dimension among the eight learning styles is visual learner 76% while the result from interview session is also confirmed visual (24.24). In order to propose a MOOC development model that is adaptive to students learning styles, a literature study was conducted. Results of the study revealed the preferred learning styles dimensions and patterns proposed suitable for an adaptive MOOC content development model.